Fashion and the Phantasmagoria of Modernity: An Introduction to Decolonial Fashion Discourse. (18th September 2020) - Jansen, M. Angela
Abstract: Although eurocentrism in fashion studies has been contested for nearly four decades, the topic is as timely and urgent as ever. While critiques focus on symptoms such as discrimination, inequality and exploitation, the actual "decease, " the modernity/coloniality structure, persists. The way fashion, as a noun, is being defined according to a temporality (contemporaneity), a system (of power) and an industry (of capitalism) particular to modernity, coloniality is inherent to its definition. Whereas fashion as a verb, the act of fashioning the body, is of all temporalities and geographies and operates beyond the colonial difference. Decolonial fashion discourse constitutes a framework that enables to redefine fashion as a multitude of possibilities rather than a normative framework falsely claiming universality, to humble modernity's narrative by recognizing its own epitomical limits, to listen to and acknowledge an episteme plurality outside of modernity and to decenter the production of knowledge in regard to fashion. It aims to critique the denial and erasure of a diversity of ways to fashioning the body due to unequal global power relations based on modern-colonial order, the Euro-American canon of normativity and the exploitation and abuse of cultural heritages, human beings and natural resources.